Q: What is the correct answer to 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 plus 1 x 0 plus 1?

Write your answer...

Submit

Related questions

x = x + 1Subtract 1 from both sides:0 = 1Well, 0 = 1 is not correct, so this equation has no solution.

2 x 0 x 1 + 1 = 0 + 1 = 1

X + 1 - x - 1 = 0, for all x. Regroup: (x - x) + (1 - 1) = 0 + 0.

x^2 + x = 0 x(x+1) = 0 x = 0 and x = -1

x = 0

x^2 + 1 = 0 x^2 - (-1) = 0 x^2 - i^2 = 0 (x - i)(x + i) = 0 x = i or x = -i

x = -1/2 or -5 2x2 + 11x + 5 = 0 ⇒ (2x + 1)(x + 5) = 0 ⇒ (2x + 1) = 0 → x = -1/2 or (x + 5) = 0 → x = -5

x + 1 = 0Subtract 1 from each side:x = -1

1 ***** 1 is not correct. The correct solution is x = -1 or -6. You can easily find it this way: Factorising, we obtain x2 + 7x + 6 = (x + 1)(x + 6) = 0. The above is true if, and only if, either, x + 1 = 0, or, else, x + 6 = 0; that is, if x = -1 or -6, which is the answer we sought. The rule is that two numbers multiply to give a product of zero, if, and only if, one of the two numbers is zero. To check our answer, let's try substitution into the original equation: Does (-1)2 + 7(-1) + 6 = 0? We see that 1 - 7 + 6 = 0. Does (-6)2 + 7(-6) + 6 = 0? We see that 36 - 42 + 6 = 0. The answer is yes, both times, thus assuring us that we have found the correct answer.

(because zero time 1= 0 plus 1)

(x+1)(x+4) = 0

(x + 6)(x + 1) = 0 so x = either -1 or -6

x2+12x+11=0 (x+11)(x+1)=0 x=-11 or x=-1

...if you did not recognize this to be (x - 1)^2... x^2 - 2x + 1 = 0 or x^2 - x - x + 1 = 0 x(x - 1) - 1(x -1) = 0 (x - 1) (x - 1) = 0 x = 1

what is the domain of g(x) equals square root of x plus 1? √(x+1) ≥ 0 x+1≥0 x≥-1 Domain: [-1,∞)

x2 + 4x + 3 = 0 (x + 1)(x + 3) = 0 x ∈ {-3, -1}

It is: 50*50*0+1 = 1

-x2+2.5x+1=0 x=-0.350781 x=2.85078

x2-x3+2x = 0 x(-x2+x+2) = 0 x(-x+2)(x+1) = 0 Points of intersection are: (0, 2), (2,10) and (-1, 1)

Both of these methods are correct:(1 x 103) + (0 x 102) + (0 x 101) + (0 x 100)(1 x 1000) + (0 x 100) + (0 x 10) + (0 x 1)

2x2 + 7x + 3 = (2x + 1)(x + 3)If 2x2 + 7x + 3 = 0 then:(2x + 1)(x + 3) = 0⇒ (2x + 1) = 0 → x = -1/2or (x + 3) = 0 → x = - 3

x2+1/4x = 0 x(x+1/4) = 0 Therefore: x = 0 or x = -1/4

1 x 8 plus 0 x 4 plus 0 x 2 plus 1 x 1. Total 9

x^0 + x=1+x=x+1

x= -1 answer: 0